Perencanaan Dan Analisis Ekonomi Pembangkit Listrik Tenaga Surya (PLTS) Terpusat Untuk Desa Mandiri - Winardi, Bambang; Nugroho, Agung; Dolphina, Erlin (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2019)
Solar cell or photovoltaic became one of the renewable energy which has great potential to be applied in Indonesia. Kaliwungu used communal photovoltaic system source of electrical energy., used load data in Kaliwungu to determined the capacity solar systems (photovoltaic array, battery, charge controller, and inverter), the potential reduction of carbon dioxide emissions, cost, and economic analysis. Economic analysis is used to evaluated the continuity of the photovoltaic system. Analysis used several methods NPW (Net Present Worth), ACF (Annual Cash Flow analysis), B-CR (Benefit-Cost Ratio analysis), FW (Future Worth analysis), and PP (Payback Period). Calculated used software MATLAB 2008a. The result shows to supply the daily load at 8,922 kWh can be supplied from the photovoltaic system with a capacity up to 2,85 kWp, battery at 464,678 Ah, charge controller up to 60 A, and the inverters at 3500 W. For the potential carbon dioxide emissions reduction up to 3,640 ton CO2. The value Rp -266.351.000,00 for NPW, Rp -23.894.600,00 for ACF, Rp 714.063.000,00 for FW, B-CR was 0.3850, and 29 years for PP.